Gadara, Jordanien: Das „Gadara Region Project“ - Kenkel, Frauke (e-Forschungsberichte des DAI, 2023)
A central aspect of any excavation is the documentation. The excavation and the removal of layers irrevocably destroy the contexts. That makes it necessary to document all the finds and features exactly and in as much detail as possible, so that conclusions are comprehensible in hindsight and it is possible to correct any misinterpretations. That is why the “Gadara Region project” is focused since 2011 on the publication of all results of the eighteen excavation campaigns that took place between 2004 and 2011 as well as the ones from the survey conducted in 2001 on the tell and the hinterland survey between 2009 and 2012. The fourth documentation campaign took place from May to June 2015.